ADHD, PHYSICAL ACTIVITY, AND INCLUSION IN VITÓRIA: A PEDAGOGICAL AND COMPARATIVE READING OF THE STUDY BY V. F. DAMIÃO AND K. G. CASTOR, FROM AN ECOLOGICAL/LIBERTARIAN PERSPECTIVE - Bozzato, Alessandro (International Journal of Engineering Technologies and Management Research, 2025)
This article offers a pedagogical and comparative reading of a study conducted by Vitor França Damião and Katia Gonçalves Castor in an elementary school in Vitória (Brazil), which analyzed the role of physical activity in the neuropsychomotor development of children with ADHD. The study not only provides objective evidence of the cognitive and socio-relational benefits of physical activity, but also highlights the structural and institutional challenges in integrating ADHD into educational systems. A comparison with the Italian context reveals both similarities and divergences. In both Brazil and Italy, ADHD is characterized by diagnostic complexity, fragmented institutional responses, and an ongoing tension between clinical and educational perspectives. While Italy benefits from a more established normative framework, it also risks excessive standardization and bureaucratization, whereas Brazil demonstrates creative practices in the absence of formal guidelines. The analysis shows that physical activity should not be seen as an ancillary or compensatory intervention, but as an integral pedagogical device capable of fostering self-regulation, attention, executive functions, and social competences. Drawing on ecological (Bronfenbrenner), socio- cultural (Vygotskij, Freire, Epstein), libertarian (Kropotkin, Faure, Reclus, Malatesta, Illich, Foucault), and complex thought frameworks (Morin, Kuhn), as well as recent neuroscientific insights (Segev, Laborit), the article argues for an inclusive and ecological approach to ADHD. The conclusion emphasizes that physical education, when designed as a cooperative and socially mediated environment, represents a structural component of inclusive education. Rather than correcting deficits, it creates conditions for participation, relational growth, and the emergence of individual potential.